2013
DOI: 10.1002/jclp.21996
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Five Facet Mindfulness Questionnaire (FFMQ): Construction of a Short Form and Evidence of a Two‐Factor Higher Order Structure of Mindfulness

Abstract: Our findings are relevant both with regard to conceptual issues on mindfulness and the assessment of mindfulness with the FFMQ. Replications in meditating samples and in patients are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

34
176
2
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(221 citation statements)
references
References 38 publications
34
176
2
9
Order By: Relevance
“…Despite this difference, the evidence regarding the construct validity of the FFMQ-BR has been confirmed since the new factor structure considerably explained the total variance of the scale (49.56%), even greater than the variance explained by the structure of the five factors in its original version, which was 33% (Baer et al, 2006). Moreover, the values of the items factor loadings were satisfactory with an average of 0.58, in comparison with the other validations, wherein the factor loadings ranged from 0.31 to 0.92 (Christopher, Neuser, Michael, & Baitmangalkar, 2012;Tran et al, 2013;Veehof et al, 2011). The version with the seven factors was given by dividing two of the original factors into other two parts, and was approved by the author of the original instrument.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Despite this difference, the evidence regarding the construct validity of the FFMQ-BR has been confirmed since the new factor structure considerably explained the total variance of the scale (49.56%), even greater than the variance explained by the structure of the five factors in its original version, which was 33% (Baer et al, 2006). Moreover, the values of the items factor loadings were satisfactory with an average of 0.58, in comparison with the other validations, wherein the factor loadings ranged from 0.31 to 0.92 (Christopher, Neuser, Michael, & Baitmangalkar, 2012;Tran et al, 2013;Veehof et al, 2011). The version with the seven factors was given by dividing two of the original factors into other two parts, and was approved by the author of the original instrument.…”
Section: Discussionmentioning
confidence: 64%
“…The choice for the FFMQ was based on the review of the scientific literature, once this instrument is one of the most cited measures to assess mindfulness (Sauer et al, 2013). In addition, the FFMQ was adapted and validated in at least six countries to date being able to measure levels of mindfulness in a wide range of populations with or without meditation experience (Baer et al, 2008;Cebolla et al, 2012;Dundas, Vøllestad, Binder & Sivertsen, 2013;Hou, Wong, Lo, Mak, & Ma, 2013;Sugiura, Sato, Ito, & Murakami, 2012;Tran, Glück, & Nader, 2013;Veehof, Klooster, Taal, Westerhof, & Bohlmeijer, 2011).…”
mentioning
confidence: 99%
“…Previous research showed that Observe correlates slightly positively with symptoms of depression and anxiety in nonmeditating samples (e.g., Baer et al 2006;Tran et al 2013), possibly reflecting ruminative tendencies (i.e., repetitive thinking about negative outcomes). Only among meditators, all five facets of the FFMQ were consistently negatively associated with psychological symptoms (Baer et al 2006(Baer et al , 2008Tran et al 2014).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 93%
“…They also allow for a parsimonious examination of the associations of the multi-facetted construct of mindfulness with other constructs, as the two higher-order factors of the FFMQ subsume all of its five lower-order factors. Observe and, among meditators, Nonreact and Describe were found to be specifically indicative of SRA, whereas Actaware and Nonjudge of OTE (Tran et al 2013(Tran et al , 2014. Structural differences between meditators and nonmeditators in the single-factor model were quantified by the strength of association between SRA and OTE in the two-factor model.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 95%
See 1 more Smart Citation